Indian Labour Laws are undergoing a Paradigm Transformation - Adhikary, Sudipta; Banerjee, Kaushik (INTI International University, 2022)
The administration of the National Democratic Alliance, which was elected on the basis of a "public promise" of development, is pursuing labour deregulation aggressively. In light of the government's efforts to weaken the three key labour laws governing industrial relations—the Trade Unions Act of 1926, the Industrial Employment (Standing Orders) Act of 1946, and the Industrial Disputes Act of 1947—this article outlines some notable modifications to the laws. It also emphasises Indian trade unions' defensive posture, which arises from the government's hurry to change labour rules.